Impact of preparation using conventional and modified density gradient centrifugation methods on sperm concentration, motility and number of normal motile sperm recovery (nmsr) - Yudiwati, Rina; Pramesti, MPBD; Agustinus, Agustinus; Pradana, E; Purwanto, Bambang (Folia Medica Indonesiana, 2017)
Some preparation techniques, either conventional or advanced, have been provided. Advanced technique may overcome the limitations of conventional techniques. Recently, not all fertility clinics in Indonesia are able to provide advanced preparation techniques. Some techniques require expensive equipments and can only be used for intracytoplasmic sperm injection (ICSI). Some fertility clinics use a modified procedure, namely the combination of density gradient centrifugation with a swim-up method for the preparation of the sperm to be used in ART. This study aimed to determine whether the modified density gradient centrifugation, which is density gradient centrifugation followed by a swim-up, is able to yield better results than conventional density gradient centrifugation. This study was a laboratory experimental pre and pos-test control group design. Population was all adult men aged 21-40 years old and the sampling unit was the man donor's semen which fulfilled inclusion criterias, collected during the periode of the study. Sample size was eight. Sperm analysis were done before and after preparation in conventional and modified group. Descriptive comparation analysis have been used. This study obtained NMSR 7.9+5.5 million/ejaculate and recovery rate (RR) 27.66+11.8 %. RR was lower compared to RR obtained conventional DGC method. RR might be lower because in modified DGC samples undergo two steps selection while conventional DGC only one step selection. But conventional DGC samples should be centrifuged twice, therefore sperms might experience more trauma. Lower RR sperm does not exclude the possibility to be used for ART, because still within the required number for all TRBs. In conclusion, modified DGC preparation method obtained lower NMSR and RR, nevertheless harvested sperms can still be used in all kind of ART.